Transforming Online Learning Management: Generative Models on ChatGPT to Enhance Online Student Engagement Scale (OLE) - Al Yakin, Ahmad; Muthmainnah, Muthmainnah; Apriani, Eka; Obaid, Ahmed J.; Elngar, Ahmed A. (Institut Agama Islam Negeri Lhokseumawe, 2023)
Artificial Intelligence (AI) technology in education is rising, with ChatGPT, an advanced AI chatbot developed by OpenAI, gaining popularity. This study focuses on exploring the potential of ChatGPT in enhancing academic learning in sociology and politics. Using a quantitative research approach, the study examines student engagement with ChatGPT in an educational setting. The research was conducted with 23 fourth-semester undergraduate students in early 2023. The findings indicate that ChatGPT generates enthusiasm and high levels of student engagement, facilitating activities such as idea exchange, discussions, analysis, and motivation. However, the integration of ChatGPT in education requires well-defined strategies and pedagogical approaches that prioritize critical thinking skills and access to fact-checking resources. The study suggests future research directions to ensure the responsible use of chatbots like ChatGPT in academic environments. Although challenges exist, such as potential bias, the need for human oversight, and risks of misuse, effective management can overcome these obstacles. Leveraging AI in education offers opportunities for students to develop an early understanding of social biases, critical elements, and risks associated with AI implementation. The study concludes with recommendations for addressing these challenges and promoting the ethical use of ChatGPT in education.